Metode Komunikasi Islam Penyuluh Agama dalam Meningkatkan Ibadah Masyarakat Kecamatan Simpang Empat Kabupaten Asahan - Sambas, Nayla Aidilla (Lembaga Yasin AlSys, 2023)
The purpose of this research is to find out how Islamic communication methods for religious instructors increase the worship of the people of Simpang Empat District, Asahan Regency and to find out what the supporting and inhibiting factors are for religious instructors in increasing the worship of the people of Simpang Empat District, Asahan Regency. This research was conducted at the Religious Affairs Office Jl. Pioneer of Simpang Empang, Simpang Empat District, Asahan Regency. This research uses a qualitative research method with a descriptive approach, namely research that attempts to collect data, process, analyze and interpret qualitatively and describe or illustrate a number of variables relating to the problem and unit being studied. The informants for this research consisted of 1 person from the head of the KUA, Simpang Empat District, Asahan Regency, 4 people from religious instructors in Simpang Empat District, Asahan Regency and 2 people from the community of Simpang Empat District. Data collection techniques used were observation, interviews and documentation. The results of this research are that the condition of community worship is quite good, but some are poor, due to economic factors and not having free time to carry out worship. Apart from that, this increase in worship shows that the Islamic communication method used by religious instructors to increase community worship is using tabligh and bayan methods. This is proven by the increase in worship activities of the Simpang Empat sub-district community in carrying out the five daily prayers, reading the Al-Qur'an, and attend the local taklim assembly. These two methods are the pillars of success in increasing public worship.